Optical Pollution and its Effect on Man and Environment in Al- Kut City - Jabir H .Al-asadi (Al-Qadisiyah Journal of Pure Science, 2017)
The present paper is a practical, field study of optical pollution ( or, as it is Some times called, lighting pollution),that is, the effect of lights and colours on man and his environment in Al-Kut City.The study focuses on the causes of this kind of pollution, such as lights,colours,randomly designed buildings and streets, crowded market places,as well as illegal trespassing of public properties.It also discusses the lack of laws and regulation to be followed in this respect, and the effects of this pollution on the biological and psychological condition of man.The study surveyed several government departments and some universities that are concerned with this problem. It Two measurement devices were used. They are the Laser Power Meter and the Solar Power Meter.